The Nexus Between Service Encounter Perfomance and Brand Evangelism - David Amani (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
Despite its usefulness in business settings, very little is known about branding in the lens of higher education. The purpose of this study was to examine special critical incidents during service encounter performance which can trigger brand evangelism. The study adopted a cross-sectional survey research design, data were collected through administering semi-structured questionnaires to 241 students of one public university in Tanzania. Structural Equation Modelling was used to analyse data due to its strength in testing relationship between variables with multiple measurement items. The findings reveal that, service encounter performance that create unique memorable experience is very useful in triggering brand evangelism. It is recommended that, the best model of HEIs branding should consider students as the central point to HEIs brand. Therefore, HEIs should strive to proselytize students to be brand evangelists by ensuring that each service encounter produce critical incidents that create memorable experience and eventually loveto HEIs brand.